Real Time Flyover Monitoring System Using MPU6050 and LoRa: Sistem Pemantauan Jembatan Layang Secara Real-Time Menggunakan MPU6050 dan LoRa - Aflaq Puji Asmoro; Shazana Dhiya Ayuni (Indonesian Journal of Innovation Studies, 2026)
General Background Structural health monitoring is essential to ensure the safety and durability of infrastructure such as flyovers, especially under environmental and operational loads. Specific Background Sensor-based monitoring systems using accelerometer and gyroscope data provide an approach to detect structural vibrations and movements in real time. Knowledge Gap However, the integration of MPU6050 sensors with LoRa communication and cloud-based monitoring platforms for continuous flyover monitoring remains limited. Aims This study aims to design and implement a structural health monitoring system for the Sumokali Flyover using MPU6050 sensors, LoRa communication, and Google Sheet for real-time data visualization. Results The system successfully measures vibration and movement across three axes (X, Y, Z) and classifies structural conditions based on threshold values, with testing results showing normal status and 0.0% crack alert under safe conditions. Novelty The study presents a prototype integrating wireless LoRa communication and cloud-based monitoring without requiring continuous internet connectivity at the sensor node. Implications The system offers a practical solution for continuous infrastructure monitoring and early detection of structural anomalies to support maintenance and safety management. Keywords: Structural Monitoring, MPU6050 Sensor, LoRa Communication, Internet of Things, Flyover System Key Findings Highlights Sensor readings remained within safe thresholds during testing conditions Wireless transmission enables remote observation without direct connectivity Threshold-based classification provides early indication of structural condition